Exploring the Landscape of work readiness in vocational students: A Bibliometric Analysis - Baandaalr Lizein; Hari Mulyadi; Endang Supardi; Fadli Agus Triansyah (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2024)
The aim of this research is to determine the trend of publications related to internships in student work readiness in the last three years after the Covid-19 pandemic. The database used is Scopus. The method used is bibliometric descriptive analysis. The research stages included identification, screening, eligibility assessment, and inclusion, resulting in 152 publications as final data. The research results show that the number of publications related to work readiness has increased in the last few years after the pandemic. Australia has a significant influence on research in this area compared to other countries. In the context of the COVID-19 pandemic which is also present in the data (